Fetal Membranes Contribute to Drug Transport across the Feto-Maternal Interface Utilizing the Breast Cancer Resistance Protein (BCRP) - Ananthkumar Kammala; Meagan Benson; Esha Ganguly; Enkhtuya Radnaa; Talar Kechichian; Lauren Richardson; Ramkumar Menon (Life, 2022)
During pregnancy, the placenta is established as a primary organ for drug transport at the maternal-fetal interface. The fetal membranes (FM) also form an interface with maternal tissues; however, their role in drug transport has not been previously investigated. Knowledge of drug transport across this feto-maternal interface along with the placenta can improve new drug development and testing for use during pregnancy. We also hypothesize that extracellular vesicles (exosomes 30–160 nm) released from the FM and placental cells may also contain drug transport proteins and might impact drug trafficking across the feto-maternal interfaces. The objectives were to (1) localize the breast cancer resistance protein (BCRP) in human FM; (2) determine the drug transport function of BCRP in chorion trophoblast cells (CTCs) of the FM; and (3) investigate the presence of BCRP in FM cell-derived exosomes, as a paracrine modifier of the tissue environment for transport functions. The gene and protein expressions of ABCG2/BCRP in FMs were determined by quantitative real-time PCR (qRT-PCR) and western blotting (WB) and were localized by immunohistochemistry (IHC). The surface expression of BCRP in FM cells was determined by flow cytometry. The functional role of BCRP was assessed by an EFFLUX dye multidrug resistance assay. The presence of BCRP in exosomes derived from CTCs and BeWo cells was examined using ExoView®. Data derived from CTCs are compared with placental trophoblast cells (BeWo). BCRP is expressed and localized in the fetal membrane, primarily in the chorion trophoblast cell layer and scarcely in the amnion epithelial layer (AEC), and primarily localized on both AEC and CTC cell surfaces. Efflux assay data showed that FM cells have similar drug resistance activity as BeWo cells, suggesting that FM also have drug transportation capabilities. BeWo- and CTC-derived exosomes expressed limited BCRP protein on the surface, so it was predominantly contained in the exosomal lumen. As far as we are aware, this is the first study to report BCRP expression in fetal membrane cells and as cargo in fetal membrane-derived exosomes. We report that fetal membrane cells are capable of drug transportation. Based on these results, investigational drug trials should include the FM and its exosomes as possible drug transportation routes in pregnancy.